Response of Abundance and Distribution of Humboldt Squid (Dosidicus gigas) to Short-Lived Eddies in the Eastern Equatorial Pacific Ocean From April to June 2017 - Fang, Xingnan; Yu, Wei; Chen, Xinjun; Zhang, Yang (Frontiers in Marine Science, 2021)
In this study, the eddy characteristics on the fishing ground of the Humboldt squid (Dosidicus gigas) in the eastern equatorial Pacific Ocean were detected based on geometrical characteristics with the flow field during April–June 2017. The influence of the eddies on the biophysical environment, D. gigas abundance, and habitat distribution were explored. The habitat was identified by fishery data, sea surface temperature (SST), vertical water temperature, and chlorophyll-a (Chl-a). Results indicated that the eddy lifetime was relatively short, with only three eddies persisting for more than 2 weeks. The number of eddies in each month showed a similar variability trend with the monthly average catch per unit effort (CPUE) of D. gigas. Two eddies were taken with a lifetime of above 2 weeks, which revealed that the environmental conditions around the eddies significantly changed. When the eddy persisted for 8–10 days, SST and vertical temperature gradually decreased, but Chl-a significantly increased. The habitat quality of D. gigas gradually increased, and the gravity center of the fishing ground was consistent with eddy movement. The eddy-induced Ekman pumping led to the transportation of deep waters with rich nutrients into the euphotic layer, promoted the reproduction of bait organisms, and yielded favorable water temperature conditions for D. gigas. These environmental changes aided the formation of high-quality habitats, which increase D. gigas abundance and catch and drive the shift of the gravity centers of fishing grounds with the eddy. Our findings suggested that eddy activities have significant impacts on D. gigas abundance and habitat distribution.